Empathic accuracy and oxytocin after tryptophan depletion in adults at risk for depression. - Hogenelst, Koen; Schoevers, Robert; Kema, Ido; Sweep, Fred; Rot, Marije (Psychopharmacology, 2016)
Rationale: Major depressive disorder (MDD) has been associated with disturbances in social functioning and in the brain serotonin system. Reduced levels of serotonin may negatively influence social functioning, for example by impairing the recognition of facial emotion expressions. Objectives: The present study investigated the effect of acute tryptophan depletion (ATD), which reduces brain serotonin, on a related component of social functioning, empathic accuracy (EA), and oxytocin levels. Methods: Individuals with (FH+) and without (FH−) a family history of MDD participated in a randomized, double-blind, crossover study. On two separate test days, participants ingested tryptophan-deficient and nutritionally balanced amino acid mixtures. Six hours later, they performed an EA task, which involved watching videos of people recounting autobiographical emotional events. While watching, participants continuously rated how these people felt during the recounting. Mood state was repeatedly assessed using the Positive Affect and Negative Affect Schedule and a series of visual analogue scales. Blood samples obtained at baseline and 5 h after mixture ingestion were assessed for tryptophan and oxytocin levels. Results: ATD decreased circulating levels of tryptophan and oxytocin. Nevertheless, there were no significant effects of ATD on EA or mood in either FH group. Conclusions: While previous studies have shown that acute reductions in brain serotonin alter the recognition of facial emotion expressions in never-depressed individuals, the present study suggests that empathic abilities may remain unaffected.